Offshore Central Asia: Switzerland as a Site for Political Struggles between Kazakh Elites - Lemon, Edward; Rosset, Damian (My University, 2015)
Central Asian politics increasingly takes place offshore. Kazakhstan’s recent encroachments into Swiss politics exemplify this trend. Regime-linked individuals have hired lobbyists put pressure on Swiss lawmakers to extradite exiled critics. In the following article, Damian Rosset and Edward Lemon examine Kazakh offshore politics and argue that such attempts to distort the course of justice matter.